PERWUJUDAN GOOD GOVERNANCE DALAM PROSES PEMBUATAN E-KTP DI KECAMATAN TANJUNG SENENG KOTA BANDAR LAMPUNG - Yuyun Fitriani (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by poor public services carried out by the government, one of which is in the implementation of making E-KTP. The problem that arises in making E-KTP is the lack of facilities and infrastructure owned by the government to support policy implementation. The purpose of this research is to analyze the efforts to realize the excellent service carried out by the Tanjung Glad District in the process of making E-KTP based on the principles of Good Governance. This type of research is descriptive research with a qualitative approach. This research was conducted using the method of collecting through interviews, documentation and observation. The data analysis technique used in this research is data reduction, data presentation and conclusion drawing. The results of the study were measured using nine principles of good governance based on the UNDP (United National Development Program), namely community participation, upholding the rule of law, transparency, consensus-oriented, effectiveness and efficiency, accountability. The results of the study indicate that the application of the principles of good governance in the implementation of making E-KTP in Tanjung Glad District has been implemented well, although the principles of efficiency and effectiveness have not been achieved because the making of E-KTP still takes a relatively long time. Keywords: Public Service, Good Governance, Good governance principles.